Screening, genetic diversity of aiiA gene in AHL-lactonase producing bacteria and their potential to suppress the virulence factors of Ralstonia syzygii subsp. indonesiensis - Tiara Edelwinna; Giyanto Giyanto; Abdjad Asih Nawangsih (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2025)
Ralstonia syzigii subsp. indonesiensis (Rsi) is a causal pathogen of Phylotype IV within the Ralstonia solanacearum species complex, commonly found in chili plants. This pathogenic bacterium uses a quorum sensing (QS) mechanism that relies on N-acyl homoserine lactone (AHL) signals to regulate the expression of virulence genes, such as those encoding exopolysaccharides (EPS). Biological control of Rsi can be achieved by disrupting its QS system. The aim of this study was to isolate AHL-lactonase-producing bacteria, analyze the genetic diversity of their aiiA gene, and evaluate their effectiveness in suppressing EPS production in Rsi. The research involved sampling, isolating, and screening bacterial candidates from chili plants as AHL-lactonase producers using bioassays and molecular techniques, followed by evaluation of their ability to inhibit EPS expression as a virulence factor of Rsi. Bacterial samples were isolated from Brebes, Bandung, and Garut Regencies. Molecular identification revealed that the twelve selected isolates belonged to the genus Bacillus. Sequencing results showed genetic diversity in the aiiA gene among isolates obtained from regions with different altitudes. All isolates demonstrated the ability to suppress Rsi virulence factors.